KONSELING KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN KEDISIPLINAN SHALAT FARDU ANAK ASUH DI LKSA BERKAH PALANGKA RAYA - Nurdiana Nurdiana; Desi Erawati; Dony Pratama (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2020)
Group counseling is a process of assistance provided by using group dynamics to solve problems such as problems in one of the Child Welfare Institutions (LKSA) namely discipline problems. This research that some children cannot carry out discipline in fardu prayer, for example during prayer fardu is not on time, then some children carry out fardu prayers are not in accordance with the terms and pillars of prayer, fardu prayers are not congregational, do not look special in prayer and do not have habituation in prayer. In this cases that the purpose how the disciplinary behavior of foster children, and implementation of group counseling with modeling techniques. This research uses quantitative methods and the type of research used is experimental research. The population of this study were foster children totaling 75 (seventy five) children. The sampling technique used was purposive sampling and obtained a sample of 12 (twelve) children. Data collection techniques in this study using observation, interview, documentation and Guttman scale techniques. For data analysis the level of discipline of fardu prayer foster children using the t test.The results showed that the discipline of fardu prayer before being given group counseling with modeling techniques with an average total score of 56.25% was included in the low category. After being given counseling the group with the modeling technique increased to 78.66% with a high category. so that an increase of 21.91%. Besides the data analysis t count with degrees of freedom (df) = 11 obtained t count> t table (7.811> 2,2009) or Ha accepted and Ho rejected. It can be ascertained that group counseling services with modeling techniques have effectiveness in improving the discipline of children's fard prayer